1967
DOI: 10.1136/bmj.4.5582.772
|View full text |Cite
|
Sign up to set email alerts
|

Transfer factor (diffusing capacity) for the lung in simple pneumoconiosis of coal workers.

Abstract: Fertility Control-Zafiartu BRITISH ovulatory cycles with good sperm tolerance. The tests were performed from 10 to 18 days after the last additional oestrogen tablet was taken. DiscussionThe incidence of uterine bleeding and menstrual cycle modifications in women receiving oral continuous chlormadinone acetate in microdoses is significant. In our experience 153 (39.2 %) out of 390 women presented some alterations in uterine bleeding while using this contraceptive method; amenorrhoea, for instance, was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

1971
1971
1990
1990

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 2 publications
1
13
0
1
Order By: Relevance
“…There is now good evidence that this difference is associated with lower values for the transfer factor (diffusing capacity) for carbon monoxide measured by the single breath method (Billiet and Ulburghs, 1966;Lyons, Clarke, Hall, and Cotes, 1967;Cotes, Deivanayagam, Field, and Billiet, 1972). These changes constitute two components of the syndrome of defective gas transfer (Scadding, 1966), of which the third is hyperventilation during exercise.…”
mentioning
confidence: 99%
“…There is now good evidence that this difference is associated with lower values for the transfer factor (diffusing capacity) for carbon monoxide measured by the single breath method (Billiet and Ulburghs, 1966;Lyons, Clarke, Hall, and Cotes, 1967;Cotes, Deivanayagam, Field, and Billiet, 1972). These changes constitute two components of the syndrome of defective gas transfer (Scadding, 1966), of which the third is hyperventilation during exercise.…”
mentioning
confidence: 99%
“…Reduction of the transfer factor has also been reported in certain types of simple pneumoconiosis both from the Continent (Englert and De Coster, 1965) and from Great Britain (Lyons et al, 1967;Cotes et al, 1970). Rasmussen and Nelson (1971) reported results of lung function tests, including studies of both ventilation and gas transfer, in 368 Appalachian soft-coal miners.…”
Section: Introductionmentioning
confidence: 82%
“…When DL was divided by total lung capacity, those with p opacities had abnormally low values compared to the authors' normal controls. Lyons, Clarke, Hall, and Cotes (1967), using the single breath technique, found lower values for DL in those of their subjects with p than in those with q opacities, but when corrected for differences in cigarette smoking between the two groups, this finding lost its statistical significance. These authors also found that the group with a lower DL had a significant reduction in pulmonary capillary blood volume and in diffusing capacity of the membrane.…”
Section: Detailed Studymentioning
confidence: 91%